Colombia : works for taxes - Elias, Jaan; Jiménez, Nicolás; MacDonald, Greg; Shapiro, Ian (London : Yale School of Management, 2020)
When the FARC-EP (Fuerzas Armadas Revolucionarias de Colombia - Revolutionary Armed Forces of Colombia) officially disarmed in June of 2017, a long and bloody 50-year struggle ended. The conflict had touched all areas of Colombia, but the FARC's control had been concentrated in rural regions, where the group controlled wide swaths of territory. With the end of the conflict, the federal government faced the question of how to rebuild these rural areas, labeled the Zones Most Affected by the Armed Conflict (ZOMACs).
Originally Published InElias, J., Jiménez, N., MacDonald, G., & Shapiro, I. (2020). Colombia: Works for Taxes. 20-026. New Haven, CT: Yale School of Management, Yale University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Colombia -- Social conditions